Predicting the ice clearing capacity of Lac St-Pierre. - Morin, Isabelle. (University of Ottawa (Canada), 2000)
Lac St-Pierre is particularly prone to ice jams that create difficult conditions for navigation on the shipping channel. In this project, a mathematical model was used to determine the ice clearing on Lac St-Pierre under various conditions. The particle-dynamics model Pdyn was applied to simulate a wide range of channel configurations and ambient environmental conditions. Relationships between ice movement and ambient conditions were then developed by aggregating the results from a large number of simulations. The relationships obtained quantify the relative impact of various parameters, such as the channel geometry, floe size, ice concentration, and wind, on ice velocity and flux. And since it makes use of readily measurable field data, the mathematical model is particularly valuable for inclusion into an integrated ice management system.
Keywords: Engineering, Civil.